RANCANG BANGUN ALAT PENGUKUR TINGGI BADAN DIGITAL MENGGUNAKAN SENSOR ULTRASONIK DAN ARDUINO UNO - idham khalik idham; Raden Wirawan; Nurwahid Syam (Institut Teknologi dan Bisnis Bina Adinata, 2025)
This study aims to: (1) Design a digital height measuring device using ultrasonic sensors and arduino uno. (2) Knowing the user response of digital height measuring devices using ultrasonic sensors and arduino uno. This research uses the Research and development method: (R & D) is research that aims to produce and is focused on producing products using 6 stages, namely Observation, Design, Building Tools, Validation, Testing Tools, Using Tools. The results of the study: (1) As for how to design a digital bandan height measuring device using an ultrasonic sensor and Arduino Uno, namely making a design then assembling the tool, doing the programming, then doing the testing, then validating or repairing the tool, then testing the tool after that the tool is used. (2) Research results: From user responses to digital bandan height measuring devices using ultrasonic sensors and Arduino uno used at Posyandu Asoka III Ultrasonic sensors, Arduino Uno and LCD, can detect and process data and display values ​​or can work properly.